Kenaf: renewable source for biopolymer - Anuar, Hazleen; Mel, Maizirwan; Mohamed, Nurhafizah Seeni; Mohd. Nasir, Nur Aimi; Mustafa Kamalbhrin, Mohd. Adlan (2011)
Nowadays, most polymers are derived from non renewable resources such from crude oil which is not environmental friendly. This has led to the research on producing biodegradable polymers which is polylactic acid (PLA) from 100% renewable sources such as plant with good properties. Lactic acid (LA) is the basic building monomer in PLA construction. Traditionally, the raw material that been used in LA production are obtain by using starch or cellulose from the plant. The common types of starch used are from field corn, wheat and many more which considered as less economical since they have to compete with the food sources industries. Kenaf (Hibiscus cannabinus, L.) is found to be the best alternative plant to substitute the raw material for LA production due to its short period of harvest time and process high quality cellulose. It is a lignocellulosic material which is naturally resistant to breakdown to its structural sugars that will inhibit microorganisms to be accessed through. Thus, it needs to undergo pre-treatment process either by mild acid hydrolysis or base hydrolysis in order to liberate glucose. Three solvents namely sodium hydroxide (NaOH), sulphuric acid (H2SO4) and ammonium hydroxide (NH4OH) were used to determine the best method for pre-treatment process. Sulfuric acid was found to give highest percentage of glucose conversion which is 9.83% or 2.95 g/L glucose. Further, the optimization process was carried out by using sulphuric acid as it main solvent. From this process, 8.65 g/L of glucose have been produced, which equivalent to 21.63% of glucose conversion. Then, the fermentation process was conducted by using Lactobacillus rhamnosus as microbes to produce lactic acid. After the fermentation process, the lactic acid will be then purified and synthesis into polylactic acid via polycondensation method.